TEST ANXIETY, COMPUTER SELF EFFICACY, AND PERCEIVED EASE OF USE DURING COMPUTER-BASED TEST ON FIRST-YEAR STUDENTS (Proceedings of the International Conference on Education, 2019)
This study aims to provide description of psychological factors such as test anxiety, computer self-efficacy, and perceived ease of use in completing computer-based tests (CBT) on first-year students. Such study is important because for first year students from different regions, not all of them have experience of CBT and there are possibilities of various psychological aspects such as CBT anxiety, Computer Self-Efficacy, and perceived ease of use affecting them in completing CBT. The subjects are 203 first-year students of Faculty of Psychology Universitas Airlangga. Scales used in this research include an adaptation of Computer Self-Efficacy scale by Compeau, DR, and Higgins, CA (1995), Test Anxiety Inventory (TAI) by Taylor and Diane (2002), Perceived Ease of Use scale by Davis (1989). The results showed that the student’s test anxiety test during CBT are categorized as 16.74% low, 76.26% moderate and 7% high. Regarding computer self-efficacy, about 28.57% students had low efficacy, 59.60% with mediocre efficacy and 11.82% had high efficacy. In term of perceived ease of use of the CBT, 2.46% perceived low ease, 34,48% perceived moderate degree of ease, while 63,05% perceived high ease of use.
Keywords: Computer self-efficacy; test anxiety; perceived ease of use